2005
DOI: 10.1136/gut.2005.079392
|View full text |Cite
|
Sign up to set email alerts
|

Fontolizumab, a humanised anti-interferon   antibody, demonstrates safety and clinical activity in patients with moderate to severe Crohn's disease

Abstract: Introduction: Interferon c is a potent proinflammatory cytokine implicated in the inflammation of Crohn's disease (CD). We evaluated the safety and efficacy of fontolizumab, a humanised anti-interferon c antibody, in patients with moderate to severe CD. Methods: A total of 133 patients with Crohn's disease activity index (CDAI) scores between 250 and 450, inclusive, were randomised to receive placebo or fontolizumab 4 or 10 mg/kg. Forty two patients received one dose and 91 patients received two doses on days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(104 citation statements)
references
References 8 publications
6
94
0
4
Order By: Relevance
“…IFN-γ from T H 1 cells and IL-17 from T H 17 cells are both key mediators in several autoimmune diseases and IBD. 5,6,20,21 In DSS-treated mice, IFN-γ, IL-17, and TNF-α mRNA ( Figure 1E) and protein ( Figure 1F) expressions were significantly higher than in untreated mice. However, IL-4 produced by T H 2 cells was rarely detectable in this model (data not shown).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…IFN-γ from T H 1 cells and IL-17 from T H 17 cells are both key mediators in several autoimmune diseases and IBD. 5,6,20,21 In DSS-treated mice, IFN-γ, IL-17, and TNF-α mRNA ( Figure 1E) and protein ( Figure 1F) expressions were significantly higher than in untreated mice. However, IL-4 produced by T H 2 cells was rarely detectable in this model (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…CD has been characterized as having a T cell helper (T H ) 1 and T H 17 cytokine pattern, and antibodies to both interferon (IFN)-γ and p40 (interleukin (IL)-12/23) can treat subsets of CD patients. 5,6 TL1A, a recently identified tumor necrosis factor (TNF)-like factor, is the only known ligand for death receptor (DR) 3 which is primarily expressed on activated lymphocytes. 7 TL1A is expressed on endothelial cells, lymphocytes, plasma cells, monocytes, and DCs.…”
Section: Introductionmentioning
confidence: 99%
“…136 Similarly, a humanized monoclonal antibody directed against IFN-␥ is well tolerated by patients with Crohn's disease and has a beneficial effect on disease activity. 137,138 Besides neutralizing antibodies or similar strategies with soluble cytokine receptors, we have recently demonstrated that the IFN-␥ axis may be inhibited in an experimental model of GA by preventing IP-10 binding to low-affinity glycosaminoglycan (GAG) sites on vascular cells and consequently decreasing the transendothelial migration and arterial recruitment of CXCR3 ϩ T H 1 cells. 139 Currently, there is a great deal of interest by a number of groups in developing synthetic GAG derivatives capable of competitively binding cytokines and chemokines 140 and in producing modified chemokines with an alteration in the GAG-binding site such that they do not oligomerize on EC surfaces.…”
Section: Strategies For Clinical Investigations To Test the Ifn-␥ Aximentioning
confidence: 99%
“…Disease Targets IFN-α Hepatitis B and C [5] IFN-β Multiple sclerosis [5] IFN-γ Chronic granulomatous disease [38], Crohn's disease [65], Multidrug resistant tuberculosis [42] TNF-α Rheumatoid arthritis [30,31], Sepsis [32], Refractory asthma [33], Psoriasis [2] G-CSF Idiopathic neutropenia, Congenital neutropenia, Febrile neutropenia, Leukemic neutropenia, Aplastic neutropenia [37], Bone marrow suppression [5] GM-CSF Bone marrow suppression, Crohn's disease [5] IL-2 Metastatic melanoma, Renal cell carcinoma [46] IL-4 Asthma [43] IL-5 Asthma [44] IL-6 Rheumatic diseases [34] IL-10 Crohn's disease, Ulcerative colitis [2], Psoriasis, Rheumatoid arthritis [5] IL-11 Crohn's disease, Ulcerative colitis, Psoriasis, Rheumatoid arthritis [2] IL-13 Asthma [2,45] Erythropoietin Anaemia, Bone marrow failure [5] HER2-Specific Monoclonal Antibody Adenocarcinoma of stomach, Breast cancer [35,36] …”
Section: Cytokinesmentioning
confidence: 99%